New records of bees (Hymenoptera: Apoidea) from the Maltese Islands - Balzan, Mario V; Genoud, David; Rasmont, Pierre; Schwarz, Maximilian; Michez, Denis (Journal of Melittology, 2017)
A total of 95 bee species have been recorded from the Maltese Islands (central Mediterranean Sea). The aim of the present note is to report newly recorded species within the study area. A total of nine new species belonging to four families are recorded here: Andrenidae (1 species), Apidae (1 species), Halictidae (5 species), and Megachilidae (2 species).